The Ubiquitin System and Kaposi’s Sarcoma-Associated Herpesvirus - Ashizawa, Akira; Higashi, Chizuka; Masuda, Kazuki; Ohga, Rie; Taira, Takahiro; Fujimuro, Masahiro (Frontiers in Microbiology, 2012)
Ubiquitination is a post-translational modification in which one or more ubiquitin molecules are covalently linked to lysine residues of target proteins. The ubiquitin system plays a key role in the regulation of protein degradation, which contributes to cell signaling, vesicular trafficking, apoptosis, and immune regulation. Bacterial and viral pathogens exploit the cellular ubiquitin system by encoding their own proteins to serve their survival and replication in infected cells. Recent studies have revealed that Kaposi’s sarcoma-associated herpesvirus (KSHV) manipulates the ubiquitin system of infected cells to facilitate cell proliferation, anti-apoptosis, and evasion from immunity. This review summarizes recent developments in our understanding of the molecular mechanisms used by KSHV to interact with the cellular ubiquitin machinery.